Effects of Counseling on Post-Operative Cataract Discharge Care in Promoting Self-Care Compliance Behavior: A Quasi-Experimental Design - Khowaja, Rozina; Syed, Binafsha Manzoor; Khowaja, Shaneela; Sarwar, Sabiha; Qureshi, Irum; Ali, Damiya Naeem (Indus Journal of Bioscience Research, 2025)
Background: Cataract-related blindness remains a significant public health concern, especially in low-resource settings like Pakistan. While cataract surgery is effective in restoring vision, post-operative self-care is critical to ensure successful recovery and prevent complications. Objective: This study aimed to evaluate the effectiveness of structured counseling sessions in enhancing self-care compliance among post-operative cataract patients. Methods: A quasi-experimental post-test design was used involving 300 cataract patients from Sindh Institute of Ophthalmology and Visual Sciences in Hyderabad from 10th June, 2024 to 10th December 2024. Participants were divided into interventional and control groups. The intervention group received structured counseling on discharge care, while the control group received standard instructions. Self-care compliance was assessed at follow-up using a structured questionnaire. Results: The interventional group showed significantly higher compliance across multiple self-care domains, including hygiene, activity restrictions, and medication adherence. Statistical analysis revealed a significant difference in compliance scores between the two groups (p < 0.05). Despite improvements, barriers such as limited literacy and socioeconomic constraints influenced long-term adherence. Conclusion: Structured counseling significantly improves self-care practices following cataract surgery and offers a cost-effective, patient-centered approach for improving surgical outcomes in resource-limited settings. Future strategies should incorporate digital tools, caregiver involvement, and community-based support to sustain long-term adherence and optimize patient outcomes.